2020
DOI: 10.3233/adr-200177
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Out the Role of the Sortilin-Related Receptor 1 in Alzheimer’s Disease

Abstract: Sortilin-related receptor 1 (SORL1) encodes a large, multi-domain containing, membrane-bound receptor involved in endosomal sorting of proteins between the trans-Golgi network, endosomes and the plasma membrane. It is genetically associated with Alzheimer's disease (AD), the most common form of dementia. SORL1 is a unique gene in AD, as it appears to show strong associations with the common, late-onset, sporadic form of AD and the rare, early-onset familial form of AD. Here, we review the genetics of SORL1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 153 publications
0
22
0
Order By: Relevance
“…We did not observe any gene sets involved in endolysosomal system function to be significantly altered in W1818*/+ brains, despite that SORL1 protein is thought to act, primarily, within the endolysosomal system (reviewed in (11)). Knupp and colleagues (47) showed that complete loss of SORL1 in neurons (and not microglia) derived from human induced pluripotent stem cells (hiPSCs) resulted in early endosome enlargement, a phenomenon previously observed in post mortem EOfAD and LOAD brains (48)(49)(50).…”
Section: No Evidence That Mutation Of Sorl1 Significantly Changes Expmentioning
confidence: 60%
“…We did not observe any gene sets involved in endolysosomal system function to be significantly altered in W1818*/+ brains, despite that SORL1 protein is thought to act, primarily, within the endolysosomal system (reviewed in (11)). Knupp and colleagues (47) showed that complete loss of SORL1 in neurons (and not microglia) derived from human induced pluripotent stem cells (hiPSCs) resulted in early endosome enlargement, a phenomenon previously observed in post mortem EOfAD and LOAD brains (48)(49)(50).…”
Section: No Evidence That Mutation Of Sorl1 Significantly Changes Expmentioning
confidence: 60%
“…Nevertheless, transcripts of the EOfAD-like allele can still be detected and so, potentially, can be translated to produce a truncated protein that may act in a dominant manner. In humans, SORL1 is alternatively spliced to generate at least five protein-coding transcripts (reviewed in [ 26 ]). The C1478* mutation, which is in exon 32 of the full length human transcript, is predicted to affect all protein-coding transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins all carry a VPS10 domain with homology to the VPS10P domain found in yeast [ 25 ]. SORL1 also belongs to the low density lipoprotein receptor (LDLR) family of proteins and contains both LDLR class A repeats and LDLR class B repeats (reviewed in [ 26 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early onset familial AD (EOfAD) cases have an age of onset before 65 years, and arise due to mutations in the PRESENILIN genes (PSEN1 and PSEN2), and the genes AMYLOID Β A4 PRECURSOR PROTEIN (AbPP) and SORTILIN-RELATED RECEPTOR 1 (SORL1) (reviewed in [7][8][9]).…”
Section: Introductionmentioning
confidence: 99%